ADAMTS-13/von Willebrand factor ratio: A prognostic biomarker for portal vein thrombosis in compensated cirrhosis. A prospective observational study. Issue 12 (December 2022) - Sacco, Monica; Tardugno, Maira; Lancellotti, Stefano; Ferretti, Antonietta; Ponziani, Francesca Romana; Riccardi, Laura; Zocco, Maria Assunta; De Magistris, Antonio; Santopaolo, Francesco; Pompili, Maurizio; De Cristofaro, Raimondo
Abstract: Background and aims: In cirrhosis, decreased portal flow velocity, thrombophilia factors, and portal hypertension are considered risk factors for portal vein thrombosis (PVT). In cirrhosis, the transformation of the stellate cells causes a progressive decrease of ADAMTS-13, while VWF multimers secretion by endothelial cells is strongly enhanced. This imbalance leads to an accumulation of ultra-large VWF multimers that in sinusoidal circulation could favor PVT both in intra- and extra-hepatic branches, mostly in decompensated cirrhosis. This prospective study was aimed at identifying possible clinical, biochemical, and hemostatic factors predictive for non-tumoral PVT in a cohort of patients with compensated cirrhosis. Methods: Seventynine compensated cirrhosis patients were prospectively followed for 48 months, receiving a periodic Doppler-ultrasound liver examination associated with an extensive evaluation of clinical, biochemical, and hemostatic profile. Results: Five patients developed PVT (cumulative prevalence = 6.3%), occurring 4–36 months after enrollment. In logistic regression analysis, the ADAMTS-13/VWF:GpIbR ratio < 0.4 was the only independent variable significantly associated with PVT (OR 14.6, 95% C.I.:1.36–157.2, p = 0.027). A Cox-regression-analysis confirmed this finding (HR = 7.7, p = 0.027). Conclusions: The ADAMTS-13/VWF ratio < 0.4 measured in compensated cirrhosis could be a reliable predictive biomarker for PVT development, paving the way to novel therapeutic strategies to prevent and treat PVT in this clinical setting.